2002
DOI: 10.1159/000057871
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Secondary Caries Lesion Progression Using Fluoride Varnish

Abstract: The purpose of this study was to determine the efficacy of fluoride varnish (FV) in inhibiting progression of secondary caries (SC). In a first experiment, human teeth, restored either with amalgam or resin composite, were exposed for 4 days to a microbial caries model. Half of each specimen was then painted with an acid-resistant nail varnish to maintain the baseline SC lesion. Specimens were then either treated with a FV (removed after 24 h) or not treated (control groups) prior to being exposed for 4 more d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Control of carious lesions is mainly related to the presence of fluoride in the oral cavity, and may not be considered as directly dependent on the amount incorporated by the tooth 6,17) , since the main mechanism of action of fluoride is dynamic, inhibiting demineralization and enhancing remineralization 4,19) . Therefore, the constant presence of fluoride in the oral cavity, in saliva or oral fluids, dental plaque and enamel, may control or even inhibit the appearance of secondary carious lesions, as well as lead to arrest of existing lesions, preventing progression of incipient lesions to formation of cavity 6,22) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Control of carious lesions is mainly related to the presence of fluoride in the oral cavity, and may not be considered as directly dependent on the amount incorporated by the tooth 6,17) , since the main mechanism of action of fluoride is dynamic, inhibiting demineralization and enhancing remineralization 4,19) . Therefore, the constant presence of fluoride in the oral cavity, in saliva or oral fluids, dental plaque and enamel, may control or even inhibit the appearance of secondary carious lesions, as well as lead to arrest of existing lesions, preventing progression of incipient lesions to formation of cavity 6,22) .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the constant presence of fluoride in the oral cavity, in saliva or oral fluids, dental plaque and enamel, may control or even inhibit the appearance of secondary carious lesions, as well as lead to arrest of existing lesions, preventing progression of incipient lesions to formation of cavity 6,22) . It should be noted that the model of caries development adopted in this in vitro study is similar to that advocated by Featherstone et al 4) , which assumes a correlation with the onset and progression of carious lesions in vivo where there is a high risk of caries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Confocal laser scanning microscopy (CLSM) presents several advantages such as not requiring a thin section nor involving radiation and can be done in shorter time [Fontana et al, 1996]. Several studies have demonstrated that CLSM is a valid technique to quantify mineral changes in smooth surface caries lesion and secondary caries lesion using area measurement [Fontana et al, 1996[Fontana et al, , 2002Gonzá lez-Cabezas et al, 1998]. In this current investigation, the severity of secondary caries lesions was determined with the CLSM technique to measure the area of fluorescence.…”
mentioning
confidence: 96%